Mobile Learning and the Future of Microlearning: Revolutionizing Education with Smartphones and Apps - Sikarwar, Prerana; Silawat, Sudha; Chawla, Tripat Kaur; Agrawal, Jyoti (Innovare Journal of Education, 2025)
With the availability of smartphones, notepads, laptops, and other mobile applications, mobile learning (mLearning) and microlearning have impacted and transformed concepts in present-day education. In this study, the present status, development, impact, future directions, and limitations of mLearning and microlearning have been reviewed, including their revolutionary consequences on conventional educational institutions, mental influence, and other outcomes. Here, pedagogical frameworks, advantages, and issues related to mobile and microlearning have also been discussed. The outcomes of this review have revealed that using mobile devices for education has enabled flexible, readily available, learner-centered education free from geographical and chronological restrictions. Additionally, assessing important trends such as gamification, personalized learning, different tools, and multimedia use has transformed the educational world completely in a very short period. In summary, the outcomes of the present study revealed that mLearning and microlearning are revolutionizing education, but still, for more general acceptance, worthiness, and efficient use, issues like data security and infrastructural differences must be resolved.